ANALYSIS OF THE APPLICATION OF CREDIT RISK MANAGEMENT IN MINIMIZING NON-PERFORMING FINANCING - Silitonga, Cristin Erni Juliani; Siringoringo, Magdalena Judika Br; Saribu, Ardin Dolok (Univesitas Muhammadiyah Tangerang, 2025)
The application of risk management in banking can increase shareholder value, provide information to bank managers about possible future losses, improve methods and make systematic decisions based on available information. The purpose of this study is to find out and analyze the application of risk management carried out by the bank to minimize the risk of non-performing financing at Bank Sumut KCP Sei Sikambing. The type of data used in this study is qualitative data, in the form of explanatory data on the implementation of risk management to minimize the risk of non-performing financing of Bank Sumut KCP Sei Sikambing in 2022-2024. The data analysis method used is a descriptive analysis method. The results of the study show that Bank Sumut KCP Sei Sikambing Medan has implemented credit risk management well, namely through the supervision of the board of commissioners and directors, policies, procedures and limit determination, identification, measurement, monitoring and credit risk management information system, and credit risk control. As well as conducting a customer feasibility analysis using a 7P analysis. The success of Bank Sumut KCP Sei Sikambing can be proven through an NPL ratio that does not exceed the provisions of Bank Indonesia by 5%.